Antioxidant Effect of Kenitu leaf Etanol Extract (Chrysophyllum Cainito L.) on Wistar Rat Induced Cyclophosphamid - Ekvan Danang Setya Pramudito; Erfan Efendi; Muhammad Ali Shodikin (Faculty of Medicine, University of Jember, 2019)
Recently, cancer is globally the second highest cause of death with a total death about 8.8 million in 2015. There are some therapy of cancer, one of them by using cyclophosphamid chemotherapy, but this regimen has side effects of bone marrow depression through its active metabolite of 4 hydroxy cyclophpsphamid and increase ROS which will effect on serum MDA elevation. Increased MDA serum can be prevented by giving an antioxidant or plants that have various antioxidants, such as kenitu leaves. The aim of this study was to determine the effect of antioxidants in kenitu leaves (Chrysophyllum cainito L.)) extract to MDA serum leves of cyclophosphamid-induced mice. This study used quasi experimental method with post test only controlled group design by using 1 normal control group, 1 negative control group (cyclophosphamid), and 5 treatment groups (dose of extract 50mg/kgBW; 100mg/kgBW; 200mg/kgBW; 400mg/kgBB; and 800mg / kgBW). The results of the treatment group dose 100mg/kgBB showed the average of MDA serum levels was 1.94 μg/mL which is the highest decrease in this study. The result of Kendall Tau correlation test showed the effect of kenitu leaves extract to MDA serum level had p = 0.013 and correlation coefficient = 0.431. Keywords: kenitu leaf etanol extract, cyclophosphamid, MDA serum